Pengembangan Media Imajinasi Hiragana Berbasis Android Studio Sebagai Cara Cepat Untuk Menghafal Huruf Bahasa Jepang Pada Siswa Kelas X IPA - Yulia - Yusuf (Inovasi-Jurnal Diklat Keagamaan, 2021)
The purpose of this research is to describe the process of developing an Android-based Imaginary Hiragana media, describe the quality of developing media and describe the effectiveness of using the Android-based Imaginary Hiragana media as a quick way to memorize Japanese letters. Based on the validation value of the material validator and graphic design that is equal to 76.29%, the product of this research development is good for use as a learning medium for memorizing Hiragana letters using imagination techniques. While the response or interest of students in learning Hiragana is in the positive category, this means that students of beginner Japanese language learners of class X Science show enthusiasm for learning Japanese. While the results of daily tests on "Reading and Writing Hiragana" are known that the students exceed the minimum standard of KKM. Furthermore, the response or the interest of students in learning Hiragana is positive. It means that the beginner Japanese students in class X Science show their enthusiasm in learning Japanese. In addition, the results of the post test for theme "Reading and Writing Hiragana" using T-test, shows that there are significant differences between the control class and the experimantal class. The significant value (Two Tailed) is 0,000. Because the significance value of this study is <of 0.05, so there is a significant difference between the learning outcomes of Class X Science 1 and X Science 2. This proves that the use of Hiragana Imagination media based on Android is very effective and qualified to improve student learning outcomes. This research is an R&D development research with ADDIE research model that uses analysis, design, development, implementation and evaluation.